ANALISIS FINANSIAL DAN EFISIENSI PRODUKSI USAHATANI RUMPUT LAUT DI KOTA KENDARI SULAWESI TENGGARA - , Azwir, S.P.; , Dr. Jangkung Handoyo Mulyo, M.Ec. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The successful of seaweed cultivation work is economically depending on number of input required to produce the expected result. This research aims to find out the factors that influence the seaweed farm production, efficient level of use of production factor, factors that influence the product efficiency and to find out the suitability of seaweed farm financially. Data analysis techniques used are multiple linier regression and financial suitability. Hypothesis proposed on this research are: (1) it is considered that seaweed production is influenced by number of seeds, labor loose in family, number of labor outside of family, subdivided lots wide, experience of farm, education level, input and output cost, (2) it is considered that use of production factor to seaweed farm is inefficient, (3) it is considered that efficiency of seaweed production is influenced by experience factor of seaweed farm, subdivided lots wide of seaweed farm, number of labor, and number of seed, (4) it is considered that seaweed work is appropriate financially to be worked or developed. The results of research shows that production factors (input) that have positive influence to production and productivity of seaweed in Kendari city are subdivided lost wide, number of seed, education level and location dummy. For analysis result the technical efficiency level (TER) with mean value of 1.0001 shows that the utilizing production factors (input) by seaweed farmer in Kendari City is already efficient. The analysis result of alocative efficiency (cost efficiency) the variable of subdivided lost wide, labor and number of seed is not yet allocated efficiently (inefficient). From result of profit calculation by using investment suitability criteria of NPV, IRR and B/C Ratio known that seaweed farm is beneficial and suitable to be worked and developed.